STUDY OF ALP TOXICITY ON LARVAL STAGES OF Ephestia calidella (GUEN.) A PEST OF STORED DRY FRUITS - GUPTA, SHYAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2019)
In regard to the control by fumigation of Aluminium Phosphide (AlP) was tried to suitable control measures against the Ephestia calidella (Guen.) a pest of stored dry fruits. Aluminium Phosphide was tested at different level of dosages such as Low (1 gm/ m3), Medium (2 gm/ m3) and high (3 gm/ m3) as well as different time exposures as 24, 48, and 72 hours in laboratory conditions. Aluminium Phosphide was most effective in 72 hours exposure at all dosages against all the larval stages of the pest. Toxic effects of AlP fumigation on field and godowns workers have been founded. Biological control of the pest by Bracon hebetor Say was also studied.